Influence of a short course of ritonavir used as booster in antiviral therapies against SARS-CoV-2 on the exposure of atorvastatin and rosuvastatin - Krohmer, Evelyn; Rohr, Brit Silja; Stoll, Felicitas E.; Gümüs, Katja S.; Bergamino, Mariano; Mikus, Gerd; Sauter, Max; Burhenne, Jürgen; Weiß, Johanna; Meid, Andreas; Czock, David; Blank, Antje; et al. (Cardiovascular drugs and therapy, 2025)
Early antiviral treatment with nirmatrelvir/ritonavir is recommended for SARS-CoV-2-infected patients at high risk for severe courses. Such patients are usually chronically ill and susceptible to adverse drug interactions caused by ritonavir. We investigated the interactions of short-term low-dose ritonavir therapy with atorvastatin and rosuvastatin, two statins commonly used in this population.
Veröffentlicht online: 19 December 2023
Gesehen am 01.03.2024